Combining Legal and Economic Theory. An Interdisciplinary Approach to Dutch and Polish Family Provisions in Succession Law - Beuker, Mark (Review of European and Comparative Law, 2021)
Although testamentary freedom is an important principle in succession law, legislators and judges across the world have recognized the importance of certain family members by granting them mandatory claims in the inheritance of their deceased relative (in spite of wishes of the deceased). This article focuses on these rights. The goal is to introduce the Dutch framework of imperative succession law and to demonstrate the possibilities of combining the legal and economic discipline to deepen knowledge on these provisions. Whilst examples will focus upon succession law, the concepts will be described in a general manner. This might inspire researchers to apply a similar interdisciplinary approach in other fields of law. The imperative provisions that currently exist for family members in the Netherlands can be divided into two types of claims. The first is the legitime, a fixed claim for children of the deceased. The second type are the other statutory entitlements that cover a specified range of situations in which judges have freedom in deciding upon the requests of family members. However, this discretion raises many questions on the way judges should handle such claims. A combination of law and economics can aid in describing and interpreting the law, for example by defining the need for support that is often required for a successful claim. By relying on economic data and theory, judges can come to a more consistent and substantiated way of establishing the need for support. The interdisciplinary methodology can also improve comparative legal research. The functional approach that is common in comparative legal research, assumes that law fulfills certain functions. Economic figures provide an objective basis that demonstrates what functions a law fulfills and to what extent this is done efficiently. This information can be used to compare the functioning of laws in different countries.